2018
DOI: 10.1002/acn3.534
|View full text |Cite
|
Sign up to set email alerts
|

Brain atrophy and disability worsening in primary progressive multiple sclerosis: insights from the INFORMS study

Abstract: ObjectiveTo investigate the relationship between brain volume and disability worsening over ≥3 years in the natural history of primary progressive multiple sclerosis using data from the placebo group of the INFORMS trial (n = 487; clinicaltrials.gov NCT00731692).MethodsMagnetic resonance imaging scans were collected annually. Brain volume loss was determined using SIENA. Patients were stratified by baseline normalized brain volume after adjusting for demographic and disease‐burden covariates.ResultsBaseline no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 27 publications
2
18
0
Order By: Relevance
“…Patients with high NfL at BL had a higher on-study PBVC for up to 120 months. This is clinically relevant because NBV has been shown to predict long-term outcomes in MS. [24][25][26][27] The prognostic value of BL NfL for on-study BVL observed in the current study was broadly in line with recently published work, partly using the same data from FREEEDOMS and TRANS-FORMS. 10 Furthermore, the present results are largely consistent with the Comprehensive Longitudinal Investigations in MS at Brigham and Women's Hospital (CLIMB) 22 and Expression, Proteomics, Imaging, Clinical (EPIC) 28 studies.…”
Section: Discussionsupporting
confidence: 91%
“…Patients with high NfL at BL had a higher on-study PBVC for up to 120 months. This is clinically relevant because NBV has been shown to predict long-term outcomes in MS. [24][25][26][27] The prognostic value of BL NfL for on-study BVL observed in the current study was broadly in line with recently published work, partly using the same data from FREEEDOMS and TRANS-FORMS. 10 Furthermore, the present results are largely consistent with the Comprehensive Longitudinal Investigations in MS at Brigham and Women's Hospital (CLIMB) 22 and Expression, Proteomics, Imaging, Clinical (EPIC) 28 studies.…”
Section: Discussionsupporting
confidence: 91%
“…Miller et al . investigated the relationship between brain volume and disability worsening over ≥3 years in PP‐MS and found that the rate of brain volume loss was most rapid in the severe subgroup who experienced clinical progression and least rapid in the stable subgroup who did not experience confirmed progression.…”
Section: Discussionmentioning
confidence: 99%
“…A few relatively recent studies attempted to identify measures able to predict the clinical outcome in patients with progressive MS and found that lower baseline EDSS scores and short-term changes are associated with a higher risk of subsequent clinical worsening [19,20]. Miller et al [5] investigated the relationship between brain volume and disability worsening over ≥3 years in PP-MS and found that the rate of brain volume loss was most rapid in the severe subgroup who experienced clinical progression and least rapid in the stable subgroup who did not experience confirmed progression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1), although care must be taken before applying this threshold as a marker of ther apeutic efficacy owing to the phenomenon of pseudo atrophy (see Brain volume as an outcome measure in randomized clinical trials) 25,26 . Multiple studies have shown that short term changes (over as little as 1 year) in brain volume are predictive of clinical status (diagnosis of MS or disability status) at various follow up times in clinically isolated syndromes 27,28 , relapsing-remitting MS (RRMS) 29 and primary progressive MS [30][31][32] , either in isolation or together with lesion related parameters 33,34 .…”
Section: Global Brain Volume Measures To Define and Predict Ms Severitymentioning
confidence: 99%